2011
DOI: 10.1021/jm101435r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Designed Vascular Endothelial Growth Factor Receptor Antagonist Helical Peptide with Antiangiogenic Activity in Vivo

Abstract: Angiogenesis is a fundamental process underlining physiological and pathological conditions. It is mainly regulated by the vascular endothelial growth factor (VEGF) and its receptors, which are the main targets of molecules able to modulate the angiogenic response. Pharmaceutical therapies based on antiangiogenic drugs represent a promising approach for the treatment of several socially important diseases. We report the biological and structural characterization of a VEGF receptor binder peptide designed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
59
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 45 publications
0
59
1
Order By: Relevance
“…While BAG3 can be induced in response to stress in cells of various origin it is constitutively expressed only in a few, including skeletal muscle and the heart. Importantly it is has also been shown to be constitutive in several primary tumors and tumor cell lines (pancreatic cancer, melanoma, leukemias, and others) [ 3 , 4 ] and has been shown to play an important role in tumor biology [ 3 , 4 , 5 , 6 , 7 , 8 ]. It has been suggested that its role in tumors is due to its anti-apoptotic properties in fact BAG3 has been shown to protect cells from death through a number of mechanisms that in general involve interaction with apoptosis- regulating proteins, including the IKK gamma subunit of the NF-κB- activating complex IKK [ 5 ], Bax [ 9 ], BRAF [ 10 ] and others [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…While BAG3 can be induced in response to stress in cells of various origin it is constitutively expressed only in a few, including skeletal muscle and the heart. Importantly it is has also been shown to be constitutive in several primary tumors and tumor cell lines (pancreatic cancer, melanoma, leukemias, and others) [ 3 , 4 ] and has been shown to play an important role in tumor biology [ 3 , 4 , 5 , 6 , 7 , 8 ]. It has been suggested that its role in tumors is due to its anti-apoptotic properties in fact BAG3 has been shown to protect cells from death through a number of mechanisms that in general involve interaction with apoptosis- regulating proteins, including the IKK gamma subunit of the NF-κB- activating complex IKK [ 5 ], Bax [ 9 ], BRAF [ 10 ] and others [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…39,40 More recently, the same authors described the preparation of a new peptide analogue (Ac-KLTWQELYQLKYKGI-NH 2 ) that shows anti-angiogenic properties. 41 Both peptides bind to the membrane of endothelial cells, as observed in cellular assays, but no binding assays with isolated receptors were reported. Within the VEGF-A fragment 17-25, a Phe17 residue has been identified as key for the interaction with VEGF receptors 1 and 2, while Tyr21 and Tyr25 seem to be important for the stabilization of the α-helical structure.…”
mentioning
confidence: 99%
“…Over the last several years, we reported the structural and biological properties of several VEGFR binder peptides designed on VEGF regions involved in VEGFR recognition such as the N‐terminal helix (residues 17–25) and the β ‐hairpin encompassing residues 79–92 .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, we have described the design, structure, and functional characterization of a novel VEGF antagonist helical peptide . We showed that this peptide, MA, assumes in water a well‐defined helical conformation, binds to VEGF receptors, and inhibits the VEGF biological activity on ECs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation